Uma API para sincronização de dados, baseada em micro serviços, para o suporte ao desenvolvimento de aplicações multiplataforma offline - Canaver, Fernanda Zampieri (2017)
With the increased use of devices such as computers, tablets and smartphones by people and the diversity of platforms these devices arises the need of developing cross-platform applications, in order to the same application can be run by the user from any device. In this context, the applications must support some data synchronization mechanism so that users have access to the same information in an application independently of which device is in use. For there to be synchronization, the existence of a location on the Internet for storage and centralization of data can be required, which is accessible to all devices. The availability of Internet on devices is a critical point, especially on mobile devices, which can happen loss of connection; therefore it is important that applications deal with the issue of working offline (when there is no connection). This work proposes creation of an API based on JavaScript and HTML5 in order to support development of hybrid cross-platform applications. The features of the API include the data synchronization and offline operation of application. It also proposes the use of a web server for storage and centralization of data and the use of microservices developed in Java with Spring Boot framework to synchronize data between the API and the web server.